Productivity and Profitability of Four Crops Based cropping Pattern in Jhenaidah District of Bangladesh - Sultana, M R; Ullah, M A; Abir, S T; Rahman, M S (Bangladesh Journal of Nuclear Agriculture, 2024)
A field experiment was carried out at the farmers' field in the Kaliganj upazila for two consecutive years (2021-22, 2022-23). The experiment carried out in a multi-location testing site in the Jhenaidah district, under the Jashore region. The objective of the experiment was to enhance cropping intensity and productivity by incorporating T. Aus into the existing cropping pattern. The current cropping sequence consisted of T. Aman-Mustard-Mungbean, while the suggested cropping sequence included T. Aman- Mustard-Mungbean-T. Aus. The research findings showed that the rice equivalent yield (REY) in the suggested cropping pattern was 21 t ha-1, representing a 31.25% increased over the yield of existing pattern (16 t ha-1). The greater gross return (Tk. ha-1), gross margin (Tk. ha-1), and slightly higher marginal benefit cost ratio obtained from this four-crop-based cropping pattern suggest that the proposed pattern could be recommended for higher productivity and economic benefit in other parts of the Jashore region. Bangladesh J. Nuclear Agric, 38(1): 93-100, 2024